Water Quality Analysis of some Selected Hand-Dug Wells in Burutu Community, Delta State - Peretomode, Obiajulu (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This study investigated the bacteriological and physico-chemical properties of water in selected hand-dug wells in Burutu community, Delta state and compared it with World Health Organisation (WHO) Standard. Water samples from wells in twelve different locations were selected and subjected to filtration prior to chemical analysis. The methods of analyses were determined according to the procedure in APHA. Results obtained show that some of the parameters analyzed were within WHO (2006) guidelines for drinking while others exceeded the threshold. In relation to bacteriological contamination, the result revealed that all the sampled wells were contaminated with total and faecal coliform organisms as they exceeded WHO standard. The sampled wells had a mean of total coliform 175.16±155.73mpn from twelve samples with a range of 67 to 576 mpn. Samples across the wells varied in the range of 67, 86.00, 70 mpn for (Ambar), 110, 360, 294 mpn for (Chicoco), 112, 111, 114mpn for (Low beach) and 102, 576 and 100 mpn for (Okorodudu) quarters respectively. It also shows that none of the wells are of quality in terms of portability for drinking. However, they can be used for other domestic activities like washing of clothes and bathing.